Meta Analysis: The Effect of Contextual Teaching and Learning Model in Improving Students' Mathematical Connection Ability - A. Nurlutvia Ahmad; Fitriani Nur; Ahmad Farham Majid; Sitti Mania; Sri Sulasteri (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2022)
The research was conducted to determine the effect of contextual teaching and learning in improving students' mathematical connection ability through various previous research results. The method used is a meta-analysis with a quantitative approach. The research samples are the research articles in the form of theses, dissertations, and national journals and international journals that met predetermined criteria. The process of collecting data is conducted by following the prism flow. The data analysis technique is determining the effect size of each study using the standardized mean difference formula. Further statistics of the effect size used is the random effect model. The results of the analysis of the random-effect model show that from the various research results that have been analyzed, it is able to increase students' mathematical connection ability by 85% with very big categories. This indicates that the contextual teaching and learning model provides a huge contribution to the improvement of students' mathematical connection ability.